The Impact of Body Mass Index and Benign Prostatic Hyperplasia on Bone Health of Middle‐Aged and Older Men - Tzyy‐Ling Chuang; Pao‐Liang Chen; Malcolm Koo; Mei‐Hua Chuang; Yuh‐Feng Wang (Obesity Science & Practice)
ABSTRACT Objective Osteoporosis significantly affects older adults by reducing bone mass and increasing fracture risk, thereby impacting morbidity and mortality. This study aimed to investigate the relationship between bone mineral density (BMD), body mass index (BMI), and trabecular bone score (TBS) among middle‐aged and older men with or without benign prostatic hyperplasia (BPH). Methods A retrospective study was conducted using health examination data from male participants aged 50–98 years collected at a regional hospital in southern Taiwan. Simple and multiple linear regression analyses were employed to examine the relationships between TBS and the independent variables. A total of 3714 middle‐aged and older men were included in the analysis. Results Findings indicated that higher BMI was associated with greater BMD; however, the relationship with TBS suggested potential bone quality degradation in cases of underweight and obesity. Multiple linear regression analysis demonstrated that age, waist circumference, BMD, underweight status, and obesity were significantly associated with TBS. Conclusion This study revealed the associative relationship between BMI and bone health: higher BMI was associated with increased bone density but also related to a decline in bone quality as measured by TBS, particularly in cases of obesity. These results emphasized the importance of managing BMI to optimize both bone density and quality, especially in middle‐aged and older men with or at risk of BPH.